ПОБУДОВА ФІСКАЛЬНОЇ ІДЕОЛОГІЇ НА ОСНОВІ ДУХОВНИХ І МОРАЛЬНИХ ЦІННОСТЕЙ - Письменний, Віталій Валерійович (Науковий журнал «Світ фінансів», 2017)
Письменний В. В. Побудова фіскальної ідеології на основі духовних і моральних цінностей. Обґрунтовано необхідність переформатування фіскальної ідеології на основі чеснот сумління, свідомості й обов’язку сплачувати до бюджету законно встановлені податки, тим самим рівноцінно брати участь у фінансуванні державних витрат. Встановлено, що своєрідним провідником у цьому мають стати духовні та моральні цінності, вироблені в християнстві – одній з найдревніших і наймасовіших релігій. Зважаючи на те, що церква є тим суб’єктом, який користується високим рівнем поваги й довіри серед різних верст населення, доведено, що завдяки співпраці її, держави та громадянських інституцій можна якнайшвидше забезпечити ефективне функціонування бюджетно-податкових відносин. Письменный В. В. Построение фискальной идеологии на основе духовных и моральных ценностей. Обоснована необходимость переформатирования фискальной идеологии на основе достоинств совести, сознания и обязанности уплачивать в бюджет законно установленные налоги, то есть равноценно участвовать в финансировании государственных расходов. Определено, что своеобразным проводником в этом должны стать духовные и нравственные ценности, выработанные в христианстве – одной из самых древних и массовых религий. Учитывая то, что церковь является тем субъектом, который пользуется высоким уровнем уважения и доверия среди различных слоев населения, доказано, что благодаря сотрудничеству ее, государства и гражданских институций можно быстрее обеспечить эффективное функционирование бюджетно-налоговых отношений. Pysmennyi V. Construction of fiscal ideology based on spiritual and moral values. Introduction. Excessive share of informal relations between government and business, low financial literacy of the population, unsatisfactory tax culture have made necessary reformatting the old fiscal ideology. It can be done by the introduction in taxation the spiritual and moral values, developed in Christianity. Purpose. The purpose of the article is theoretical justification of necessity of construction fiscal ideology on the virtues of conscience, consciousness and obligation to pay taxes to budget. Methods. The author used scientific methods such as historical, abstraction, deduction, comparison, analysis, idealization, systematization and others. Results. Established that from ancient times the Christian religion produced a profound impact on the process of taxation, promoting through human values pay taxes to the budget. The instructive biblical narratives in the Gospels of Matthew, Luke and Mark, the Apostle Paul to the Romans who violate tax issues in the context of moral and ethical norms is studied. Proved that the cooperation between church, state and civil society can establish the tax mechanism – to ensure the effective functioning of the tax and buget relations. The basis of fiscal ideology should be the virtues of conscience, consciousness and obligation to pay to the budget the all legally established taxes. Conclusion. Established that taxation is an important ethical duty that has to perform every person, not because of physical or psychological coercion, but only due to public necessity. The constructive changes will be only when the fiscal ideology adopt a general Christian values enshrined in the Bible.